Cerebral autoregulation monitoring in neonates and infants after cardiac surgery with cardiopulmonary bypass - comparison of single ventricle and biventricular physiology - Methner, Marcel; Schwaneberg, Bernadett; Wikidal, Berit; Schmid, Simon; Zipfel, Julian; Iller, Maximilian; Schuhmann, Martin U.; Georgiev, Yordan H.; Magunia, Harry; Berger, Rafal; Schlensak, Christian; Nordmeyer, Johannes; et al. (Frontiers in Pediatrics, 2025)
IntroductionCardiopulmonary bypass surgery can lead to impaired cerebral autoregulation with the risk for ischemia, hemorrhage and delirium. In particular, infants with single ventricle physiology have altered hemodynamics with persistent veno-arterial shunting, cyanosis and diastolic run-off after surgery, which may have negative effects on cerebral autoregulation.MethodsCerebral autoregulation was prospectively monitored in 83 neonates and infants after open heart surgery with cardiopulmonary bypass after admission to the pediatric intensive care unit. Autoregulation indices were determined using near-infrared spectroscopy, correlating regional cortical oxygen saturation and local hemoglobin levels with invasive mean arterial pressure. Intact autoregulation was defined as cerebral oxygenation index (COx) < 0.4 and hemoglobin volume index (HVx) < 0.3. A subgroup analysis was performed between 55 infants after biventricular repair surgery and 15 infants after palliative surgery.ResultsThe mean lower limit of autoregulation was 46 ± 6 mmHg (COx) and 46 ± 7 mmHg (HVx). The optimal mean arterial pressure according to cerebral autoregulation was 56 ± 8 mmHg (COx) and 55 ± 7 mmHg (HVx). The mean upper limit was 65 ± 9 mmHg (COx) and 65 ± 8 mmHg (HVx). Intact autoregulation occurred during 84 ± 8% (COx) and 77 ± 10% (HVx) of the monitored time. No significant differences were found in autoregulation parameters between single ventricle and biventricular groups. However, the single ventricle group had significantly lower arterial and cerebral oxygen saturation.DiscussionA standardized blood pressure management may not be sufficient in children after cardiac surgery due to potentially impaired cerebral autoregulation. Therefore, cerebral autoregulation monitoring should be considered in this patient population.